An fMRI study of cognitive reappraisal in major depressive disorder and borderline personality disorder - De la Peña Arteaga, Víctor (2021)
Background. One common denominator to the clinical phenotypes of borderline personality disorder (BPD) and major depressive disorder (MDD) is emotion regulation impairment. Although these two conditions have been extensively studied separately, it remains unclear whether their emotion regulation impairments are underpinned by shared or distinct neurobiological alterations.Methods. In the present study we contrasted the neural correlates of negative emotion regulation across an adult sample of BPD patients (n=19), MDD patients (n=20) and healthy controls (HCs; n=19). Emotion regulation was assessed using an established functional magnetic resonance imaging (fMRI) cognitive reappraisal paradigm. We assessed both task-related activations and modulations of interregional connectivity (i.e., Psychophysiological Interactions, PPI). Results. When compared to HCs, patients with BPD and MDD displayed a homologous decreased activation in the right ventrolateral prefrontal cortex (vlPFC) during cognitive reappraisal. Additionally, the MDD group presented decreased activations in other prefrontal areas (i.e., left dorsolateral and bilateral orbitofrontal cortices), while the BPD group was characterized by a more extended pattern of alteration in the connectivity between the vlPFC and cortices of the visual ventral stream during reappraisal. Conclusions. Decreased activation of the vlPFC underlays emotion regulation deficits in MDD and BPD, although, beyond this finding, these groups are characterized by specific neurobiological underpinnings. Alterations in patients with MDD suggest a primary deficit in the strength of prefrontal activations, while patients with BPD are better characterized by connectivity disruptions between the prefrontal cortex and temporal emotion processing regions. These findings substantiate in neurobiological terms the different profiles of emotion regulation alteration observed in these disorders.